PSYCHOLOGICAL FACTORS INFLUENCE ON ENERGY EFFICIENCY IN HOUSEHOLDS - Zaneta Simanaviciene; Virgilijus Dirma; Arturas Simanavicius (Institute of Economic Research (IER), 2017)
Research background: Most of the studies and their authors focus on the social and economic impacts of energy-saving behavior. But they do not focus on psychological factors affecting the efficiency of energy consumption in households. Lithuania has a lack of a unified and justified opinion on psychological factors that affect the energy efficiency of households. Purpose of the article: to identify the psychological factors that influence energy efficiency in households and to identify the appropriate measures changing the individual's energy consumption behavior. Methodology/methods: was based on analysis of scientific literature and expert evaluation, when the exerts selected the most influencing psychological factors. Expert valuation also allowed to set the right conditions in which individuals are more easily assimilated by means of energy saving. The correlation and regression analysis allowed to identify a variety of factors, including the psychological impact strength. Findings: Performed analysis of variety of factors that influence household energy consumption allowed to formulate conclusions that in most cases, economic and technological factors significantly influence household energy consumption, increased energy-efficient equipment production and supply is causing an energy consumption growth in households because they are more inclined to buy and use more efficient electrical equipment, which leads to the growth of energy consumption in households. An investigation showed that the energy consumption of households is strongly influenced by some cultural and psychological factors: the greater public openness to innovation, the households tend to use energy more efficiently. Also, a significant impact on energy consumption has some psychological indicators - frequently the more pronounced neuroticism or extraversion rate. Since the research was performed only in Lithuania, in the future it will seek to carry out an investigation in several countries and to compare a various factor on the proposed measures and the efficiency of household energy consumption.
Keywords: D1; C92; Q43; Q56; 330; psychological factors; efficient use of electricity; households